2015
DOI: 10.1186/s13227-015-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and embryonic origin of the eyes in the common house spider Parasteatoda tepidariorum

Abstract: BackgroundTwo visual systems are present in most arthropod groups: median and lateral eyes. Most of our current knowledge about the developmental and molecular mechanisms involved in eye formation in arthropods comes from research in the model system Drosophila melanogaster. Here, a core set of retinal determination genes, namely, sine-oculis (so), eyes absent (eya), dachshund (dac), and the two pax6 orthologues eyeless (ey) and twin of eyeless (toy) govern early retinal development. By contrast, not much is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
108
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(135 citation statements)
references
References 72 publications
20
108
2
1
Order By: Relevance
“…It is therefore equally exciting to note a new generation of molecular developmental studies in the structurally and evolutionarily complex visual systems of chelicerates [6769], opening further testing grounds for examining the conserved roles of Otd and Pph13 in photoreceptor differentiation.…”
Section: Perspectivesmentioning
confidence: 99%
“…It is therefore equally exciting to note a new generation of molecular developmental studies in the structurally and evolutionarily complex visual systems of chelicerates [6769], opening further testing grounds for examining the conserved roles of Otd and Pph13 in photoreceptor differentiation.…”
Section: Perspectivesmentioning
confidence: 99%
“…This work has expanded our understanding of the general mechanisms by which the conserved Wnt and Hh signaling pathways interact (Royet and Finkelstein, 1997) and of the development and evolution of the eyes and dorsal head of arthropods (Posnien et al, 2010(Posnien et al, , 2011Samadi et al, 2015;Schomburg et al, 2015), and has helped in establishing parallels between head patterning across phyla. For instance, members of both the Wnt and Otx gene families are involved in anterior head/ neural tube patterning in both invertebrates and vertebrates (Lichtneckert and Reichert, 2005;Rhinn et al, 2005;Schinko et al, 2008;Steinmetz et al, 2011;Fu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Optix is required to promote retinal differentiation (Li et al, 2013). Interestingly, Optix is also expressed in the prospective dorsal head of the eye-antennal disc in a single domain (Seimiya and Gehring, 2000;Kenyon et al, 2005). We examined expression using an Optix-specific antibody, and found it to be expressed in a single anterior domain that overlaps with the aOC Eya domain but not with the IOC region ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental processes are regulated by the action of developmental gene products. While the genetic underpinnings of early spider embryonic development, such as axis formation (Akiyama- Oda and Oda 2006;Oda et al 2019;Pechmann et al 2017), segmentation (Paese et al 2018;Pechmann et al 2011;Schönauer et al 2016;Stollewerk et al 2003), or visual system development (Samadi et al 2015;Schomburg et al 2015), are being revealed these days, the genetic mechanisms regulating sex determination are entirely unclear. In general, the sex in animals can be defined by environmental cues, by genetic factors or a combination thereof.…”
Section: Developmental Genetics Underlying Sex Determinationmentioning
confidence: 99%